Pengembangan Ekstrakurikuler Pramuka yang Telah Terhenti Sejak Pandemi Covid-19 SDN 1 Pangkut Kecamatan Aruta - Khoirul Mansyah; Teti Tria Alpiana; Salsabilla Esa Adisty; Windy Dwi Latifah; Muhammad Nadzif Fathoni; Nabila Nabila; Isti Qomah (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
This activity is to develop Scout extracurricular activities at SDN 1 Pangkut. Extracurriculars are school programs that aim to develop students potential, interests and talents. Apart from that, it is also a material for improving student achievement. In its implementation, good and regular management is needed so that these extracurricular activities can run well. This research aims to determine the management of Scout extracurricular activities at SDN 1 PANGKUT after the Covid-19 pandemic. With this activity, students can practice Dasa Darma and Tri Satya. This extracurricular can discipline students to live independently and get to know the vastness of nature. This activity also provides non-academic material. The aim of this activity is to apply rows correctly and according to the directions given. Students also gain knowledge of scouting history and scouting materials. With prominent activities in improving the quality of life and environmental sustainability, Scout KKN not only provides short-term benefits, but also creates a sustainable positive impact in the long term. Scout KKN students become agents of change who not only focus on physical development, but also pay attention to social and environmental aspects, creating a better and more sustainable generation in the future. In a discussion regarding Real Work Lecture (KKN) activities with the theme of Scouting.